Cultural heritage and flexibilization of touristic production in the eastern Brazilian Amazon - Maria Augusta Freitas Costa Canal; Elcivânia de Oliveira Barreto; Milene de Cássia Santos de Castro (Via@)
This article examines the implications of “new neoliberalism,” a regulatory framework, on the arrangement of cultural heritage prompted by the liberalization of tourism in the eastern Brazilian Amazon. The eastern Brazilian Amazon encompasses the Brazilian states of Amapá (AP), Maranhão (MA), Pará (PA), and Tocantins (TO). Hence, we analyzed and surveyed key data and documents relating to the tourism sector and cultural heritage. The research revealed, through indicators such as entrepreneurship, creative production, privatization, and public-private partnerships, a localized concentration of heritage organization and tourism liberalization in the areas comprising the cities of Macapá (AP), Belém (PA), and São Luís (MA). The observed internal and external interactions in the eastern Brazilian Amazon substantiate the establishment of a “new neoliberalism” regulatory framework. This framework fuses social entrepreneurship with “neo-bohemian” local creative aspects and emphasizes “institutional commodification” via public-private partnerships. This arrangement enables the utilization of this heritage by groups entrenched in neoliberal rationality.